Study on the Chromogenic Mechanism of Violet-Red to Orange-Red Spinel - Yang Du; Ying Guo (Crystals, 2023)
In this paper, the chemical composition and spectroscopy of 38 violet-red to orange-red spinel samples were analyzed by energy dispersive X-ray fluorescence spectrometer and UV-visible spectrophotometer, based on CIE LAB color space, to explore the effects of different chromogenic ions on spinel color transition. The results show that the chroma C* is mainly controlled by the variation of color coordinates a*, and the hue angle h° is mainly controlled by the variation of color coordinates b*. Spinel can be divided into iron-bearing spinel and chromium–vanadium-bearing spinel according to their chromogenic elements, where Fe is mostly present in the form of Fe2+, which is mainly replaced with Mg2+ in tetrahedral voids, while Cr3+ and V3+ are mainly replaced with Al3+ in octahedral voids, and the level of Al content indicates the degree of isomorphism in spinel. The lightness L* of spinel decreases with increasing Cr content, and the hue h° decreases with increasing Fe and increases with increasing V content.